Prurigo Simplex or "Itchy Red Bump" Disease: Review and Case Series - Joanna Wallengren (Medical Journals Sweden, 2021)
Prurigo simplex or "itchy red bump" disease is a controversial pruritic papular eruption. The objective of this study was to delineate the diagnostic criteria for this disease. A PubMed search was performed for: "prurigo simplex", "prurigo simplex subacuta", "subacute prurigo", "chronic papular dermatitis in adults" and "itchy red bump disease". Medical charts of patients with prurigo diagnoses in a university setting were analysed. The literature search revealed 32 relevant studies (431 patients) on different aspects of the disease. Out of 50 patients with prurigo diagnoses, 5 patients (4 women, mean age at onset 54 years) matched the description in literature. Small, severely itchy papules without secondary skin lesions continued to appear for years (mean 5.6 years). Skin biopsies revealed lymphocytic perivascular infiltrates, few eosinophils and occasionally spongiosis. Treatment with long-term methotrexate or cyclosporine cleared the symptoms. Some major and minor diagnostic criteria for prurigo simplex are proposed and compared with chronic prurigo.